Future Wireless Networks and Information Systems Volume 1 - Zhang, Ying.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume contains revised and extended research articles written by prominent researchers participating in ICFWI 2011 conference. The 2011 International Conference on Future Wireless Networks and Information Systems (ICFWI 2011) has been held on November 30 ~ December 1, 2011, Macao, China. Topics covered include Wireless Information Networks, Wireless Networking Technologies, Mobile Software and Services, intelligent computing, network management, power engineering, control engineering, Signal and Image Processing, Machine Learning, Control Systems and Applications, The book will offer the states of arts of tremendous advances in Wireless Networks and Information Systems and also serve as an excellent reference work for researchers and graduate students working on Wireless Networks and Information Systems.
From the content: Recognition of Tone Signal Based on Eigenvalue Decomposition -- A grid-based Predictive Location Service in Mobile Ad Hoc Networks -- Variable Consistency Dominance-based Rough Set Approach to Security Assessment of Preference Information System -- Classification model analysis of logging image based on metafeatures -- An Adaptive Robust Fuzzy Detector for Narrowband Interference Cancellation in DS-CDMA Communications -- Multi-Hop Diversity-Based Collaborative Spectrum Sensing in Cognitive Radio -- A Video Object Extraction Algorithm based on Depth Map for Multi-View Video.
Keywords: Electrical engineering; Control engineering; Management; Computers; Communications Engineering, Networks; Control and Systems Theory; Electrical Engineering; Management; Information Systems and Communication Service